The Evaluation of Intellectual Capital and Relationship with Firm Performance: A Systematic Review and Future Research Agenda - Indriana Damaianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Theoretically, the goal of this publication is to assess the progress of research on intellectual capital and firm performance in order to identify prospects for future research agendas. The final selection of 29 publications published between 2001 and 2020 was made using a comprehensive literature review process. Emerald, ScienceDirect, and Harzing's Publish or Perish with API Key were utilized as the database sources in this study, with a set of inclusion/exclusion criteria for analysis to fulfill the paper's aim. The majority of studies have found that intellectual capital has a beneficial impact on business success. The concept has undergone extensive testing in both developed and underdeveloped nations. In the field of intellectual capital research, measuring and evaluating intellectual capital remains a difficult task. It has been measured using a variety of ways. Intellectual capital should be drawn from company strategy and related to the logic of value generation, with intellectual capital metrics being developed for individual sectors. Both financial and non-financial aspects of the firm's performance were employed to create a more realistic and holictic assessment. The importance of intellectual capital as an intangible resource for businesses in producing something and attaining success is revealed in this study.